United Nations Primer for Development - Frankel, S. Herbert (Quarterly Journal of Economics, 1952)
I. Introduction: Terms of Reference, 301. — II. The Concept of Progress, 302. — III. The Cure for Unemployment, 305. — IV. Income Aggregates as Criteria of Development, 309. — V. Development Planning, 310. — VI. The Need for External Capital, 315. — VII. Private Investment, Government Lending, and Intergovernmental Grants, 320. — VIII. Concluding Observations, 325.